Impact evaluation study for Egypt's Takaful and Karama cash transfer program: Synthesis report- Summary of key findings form the quantitative and qualitative impact evaluation studies - Breisinger, Clemens; Gilligan, Daniel O.; ElDidi, Hagar; El-Enbaby, Hoda; Karachiwalla, Naureen; Kassim, Yumna; Kurdi, Sikandra; Jilani, Amir Hamza; Thai, Giang; Goessinger, Karim-Yassin; Moataz, Yasmine; Petesch, Patti (International Food Policy Research Institute, 2018)
Since March 2015, the Government of Egypt has been providing cash to poor households through the Takaful and Karama program. The program is run by the Ministry of Social Solidarity (MoSS). Takaful supports poor families with children under 18 years of age, while Karama supports the poor elderly and disabled. For Takaful, the amount of cash that households receive depends on the number of children and their school level, while the Karama transfer is a set rate per individual. In 2018, Takaful will also begin requiring households in the program to make sure their children attend school and participate in health screenings. The program was evaluated by IFPRI, an international research organization, using both quantitative statistical methods (simple questions asked to many households during a survey) and qualitative methods (more in-depth questions asked to fewer households in longer interviews). The main goal of this evaluation was to measure and explain how the transfers affected the welfare of households in the program. In addition, the evaluation describes how well the program selection criteria work for identifying poor households.